Tuning the responsivity of monoclinic (InxGa1−x)2O3 solar-blind photodetectors grown by metal organic chemical vapor deposition. (12th August 2020) - Hatipoglu, Isa; Mukhopadhyay, Partha; Alema, Fikadu; Sakthivel, Tamil S; Seal, Sudipta; Osinsky, Andrei; Schoenfeld, Winston V
Abstract: We report on the fabrication and characterization of solar-blind photodetectors based on metal organic chemical vapor deposition grown polycrystalline monoclinic indium gallium oxide ( I n x G a 1 − x ) 2 O 3 alloys on sapphire using N2 O for oxidation. The effects of growth conditions on indium incorporation efficiency and oxygen vacancies of the ( I n x G a 1 − x ) 2 O 3 alloy, photo-to-dark current ratio (PDR), gain and responsivity of the fabricated photodetectors were investigated. The optical bandgap of the films was found to decrease due to the indium incorporation ( x = 20.3%,  17.7%,  10.6% for samples A, B, and C, respectively) into the lattice of gallium oxide. By increasing the indium content incorporated into the lattice of G a 2 O 3, we demonstrated solar-blind photodetectors whose peak responsivity increased from 0.79 A/W ( G a 2 O 3 ) to 319.1 A/W, 66.1 A/W and 27.7 A/W for samples A, B and C, respectively at 5 V applied bias with the cut off wavelength below 280 nm. Increasing in content resulted in a higher concentration of oxygen vacancies in as-grown films. Increased oxygen vacancies as a result of the change in growth conditions lead to higher photoconductive gain, higher responsivities, and lower PDR, demonstrating a trade-off between responsivity and the PDR. To the best of our knowledge, the peak responsivity value reported in this work is the highest for ( I n x G a 1 − x ) 2 O 3 based solar-blind photodetectors. Fast rise and fall times in the order of 100 ms have been measured for the photodetectors.